Study and Optimization of Palm Wood Mechanical Properties by Alkalization of the Natural Fiber (Global Journal of Science Frontier Research, 2014)
This Study is devoted to the characterization of mechanical properties of a date palm Wood fiber (DPF).We propose to measure mass loss, tensile strength, Young modulus and elongation at failure. The use of natural fibers requires specific chemical treatments to address mechanical performance due to water absorption. For this reason an alkaline (NaOH) treatment of different samples at different concentrations was carried. We submit after that the samples to a Thermo gravimetric analysis (TGA) to measure the influence of soda treatment on the mass loss. In a second time, mechanical properties were studied of untreated and treated samples. Thus we can access to the elasticity limit, tensile strength and Young modulus E. The results led us to conclude that treatment of Palm fibers with soda at different concentrations results in a significant improvement of the mechanical properties.
Keywords: mechanical properties; palm fiber; tensile strength; young modulus